SEJARAH USHUL FIQH QABLA TADWIN: ANALISIS HISTORIS DAN PENGARUHNYA TERHADAP PEMBENTUKAN HUKUM ISLAM - Almurni, Muhammad Furqon; Aen, I Nurol; Anwar, Syahrul (Fakultas Ilmu Sosial dan Humaniora, 2024)
This study aims to explore the evolution of the science of ushul fiqh prior to the written era, opening a new window into the historical and intellectual understanding of this discipline, which is often presumed absent by scholars and students in shari'ah studies. Employing a descriptive analysis methodology, this research delves into the chronological development of ushul fiqh, from its initiation period to the termination of its pre-writing phase. Through an exploration of key events and dating based on historical evidence, this research identifies the inception of ushul fiqh during the migration of Prophet Muhammad SAW from Mecca to Medina. This period, starting from the first year of the Hijrah, is significant as the Quran and Hadith began to explicitly address elements of fiqh, marking the dawn of this discipline's formation. The analysis reveals that the early formation period of ushul fiqh lasted until the beginning of the second century Hijrah, where a critical transition occurred with the commencement of documentation and writing of the science by scholars, albeit in a partial form. The findings of this study not only clarify the historical timeline of ushul fiqh but also highlight the intellectual dynamics contributing to the formal consolidation of this discipline within the shari'ah science canon.